O peixe donzela, Stegastes fuscus em poças rasas de maré : engenheiro do ecossistema ou navegador oportunista? - Albuquerque, Carolina Bellumat Borges da Silva de (2018)
Popularly known as a Brazilian damselfish, the Stegastes fuscus is recognized as a key species in infralittoral environments, acting as an ecosystem engineer due to its territorialist behavior pattern. Considering this possible effect on the coastal reef habitats, the objective of this study was to evaluate if the species had in fact some influence on tidepool reef intertidal environments, used as nursery by the species, and yet so little studied. The Vegetation Cover Rate (TCV) and the percentage of nonforage environments (sand and rock), inside and outside the territories were compared. In order to evaluate the variability of the environment independent of S. fuscus, the relative percentage of macroalgae was used throughout the months of collection. The environment was very variable, considering the physical and anthropogenic factors, S. fuscus had no influence on this variables, once the TCV in its territories was similar to the TCV in the adjacent areas. However, the territories presented less forage areas (sand and rock) than adjacent unprotected areas, which may be the result of the animal's ability to allocate its territories in areas with higher food patches, according to optimal foraging theory. In addition, it was possible to verify that, although reef environments usually present top-down control, environments of flat reefs are mainly controlled bottom-up, thus being more susceptible to the physical and anthropogenic factors, due to the little control and capacity of biological restructuring.